Investigating the effects of vibration method on ultrasonic-assisted drilling of Al/SiCp metal matrix composites - Kadivar, M.A. (Robotics and Computer-Integrated Manufacturing, 2014)
Preciseness and finished surface quality are the significant factors of final products, especially in a number of drilling processes. Burr is usually considered a negative outcome in assembly procedures. One way to reduce or remove burr and improve surface roughness in metal cutting is to employ ultrasonic vibration in the drilling process. In this paper, the effects of ultrasonic vibration on burr size reduction, drilling force and surface roughness with two different vibration systems are investigated. To this end, two vibration structures were built, one to excite the workpiece (the workpiece vibration system) and the other to vibrate the tool (the tool vibration system). Besides, the effects of amplitude, feed rate, cutting speed, and SiC particle content on the drilling process of Al/SiCp metal matrix composites are studied. In all tests TiN-coated HSS drill tools with a diameter of 5 mm bwere utilized for drilling. Based on the attained results, it was demonstrated that suitable ultrasonic vibration reduced burr height, drilling force and surface roughness more so than conventional drilling. Meanwhile, in the workpiece vibration system, enhanced surface roughness and higher drilling force were obtained as compared to the tool vibration system.